Do We Need to Close the Door on Threshold Concepts?. Issue 3 (14th June 2022) - Brown, Megan E. L.; Whybrow, Paul; Finn, Gabrielle M.
Abstract: Issue: Threshold Concepts are increasingly used and researched within health professions education. First proposed by Meyer and Land in 2003, they can be defined as ways of knowing central to the mastery of a subject. They are framed as profoundly transformative, impacting the identity of those who encounter them through irreversible shifts in an individual's outlook. Although Threshold Concepts have been identified in a multitude of educational settings across the continuum of health professions education, there has been little critique of Threshold Concepts as a theory of health professions education. Within adjacent fields critical discourse is also underdeveloped, perhaps given the educational resonance of the theory, or the way in which the theory encourages subject specialists to discuss their area of interest in depth. This commentary critically examines how Threshold Concepts have been used and researched within health professions education, applying critiques from other educational fields, to assist scholars in thinking critically regarding their application. Evidence: Three significant critiques are outlined: 1) ' The floating signifier problem' ; 2) ' The body of knowledge problem' ; and 3) ' The professional identity problem.' Critique 1, the floating signifier problem, outlines how Threshold Concept theory lacks articulation and has been inconsistently operationalized. Critique 2, the body of knowledge problem, outlines the issues associated with attempting to identify a singular body of knowledge, particularly in regard to the reinforcement of entrenched power dynamics. Critique 3, the professional identity problem, argues that the way in which Threshold Concepts conceptualize identity formation is problematic, inadequately grounded in wider academic debate, and at odds with increasingly constructionist conceptualizations of identity within health professions education. Implications: These critiques have implications for both educators and researchers. Educators using Threshold Concepts theory must think carefully about the tacit messages their use communicates, consider how the use of Threshold Concepts could reinforce entrenched power dynamics, and reflect on how their use may make material less accessible to some learners. Further, given that Threshold Concept theory lacks articulation, using the theory to structure curricula or educational sessions is problematic. Threshold Concepts are not synonymous with course learning outcomes and so, While considering Threshold Concepts may enable pedagogical discussion, the theory cannot help educators decide which concepts it applies to; this requires careful planning which extends beyond the bounds of this theory. For researchers, there are issues too with power and inconsistent theoretical operationalization, but also with the way in which Threshold Concepts theory conceptualizes identity formation, which cast doubt on its use as a theory of identity development. On balance, we believe Threshold Concept theory suffers a number of fundamental flaws that necessitate a shift from the positioning of Threshold Concepts as a theory, toward the use of Threshold Concepts as a less prescriptive reflective prompt to stimulate pedagogical discussion.